Identification of Physical Characteristics and the Change of Mangrove Region in Coastal Southern Part of Padang City, West Sumatra - Indonesia - Yatno, Triyatno Yatno; Febriandi, Febriandi; Putra, Aprizon; Kamal, Eni (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
The research about the identification of mangrove physical condition and the change of mangrove area has aims are knowing of mangrove physical condition and the change of mangrove area in the coastal region southern part of Padang city. The method used in this research is the field survey and multi-temporal satellite imagery analysis in 2001 and 2018 year. Based on the field survey at the date of August 18, 2017 generally the mangrove that found in research location i.e Rhizophora Apiculata, Rhizophora mucronata, Sonneratia alba, and Nypa. The spatial distribution of the mangrove ecosystem is dependent on the ecological conditions of the area as reflected by the types of mangrove vegetation that grows and develops in the research location. A decrease in mangrove area that occurred between of 2001 to the 2017 years i.e in the coastal region of Bungus bay i.e 5.54 ha, where the decrease in mangrove area occurred because some mangrove plants were cut down and made the settlement land, while in the region of Sungai Pisang bay happen to increase in mangrove area i.e 36.12 ha, where the increase in mangrove area occurred because of the region obstructed by big waves of the sea (protected small the islands).